PEMANFAATAN BIOMASSA KERING (KAYU) SEBAGAI BAHAN BAKAR UNTUK MENGUJI KERJA PROTOTYPE KOMPOR BIOMASSA - C. F. Mamuaja; L. Y. Hunta (Universitas Tribhuwana Tunggadewi, 2012)
The aims of this study were to evaluate prototype biomass stove by using wood fuel (dry biomass), to account number of wood fuel used to boil water, time for boil, fire of temperature, water temperature, pan temperature, hot energy and water heating efficiency. Descriptive analysis was used to evaluate prototype biomass stove by using wood fuel about 1 kg with three replicates. The evaluation showed that by using wood fuel process water boiled faster than that using fuel. To make water boiled only needed 6 minutes using 93 g of wood fuel while fire temperature was 792°C . To boil water about 2 liter using stove biomass needed 6 minutes using total fuel of 92,87 g. Fire temperature observed was 792°C, where pan wall temperature was 256°C and water temperature was 105°C. Total heat energy used to boil water was: 7336,73 cal; 2507,49 cal and 1578,79 cal. Efficieny of water heat that was calculated from water boil process by using stove biomass was 38,5%. Prototype stove biomassa needed smaller hole out of fire to make flame not so high, and adding hole of wind in side of fuel tube to make air aeration better and to control equipment volume fuel